Contracaecum ... - Arai, Hisao P.; Smith, John W. (Zenodo, 2016)
* Contracaecum sp. and/or * Phocascaris sp. Description: see that for * Contracaecum osculatum above. Sites: alimentary tract, body cavity, mesenteries Hosts: Cyclopterus lumpus (7); Gadus morhua (2, 3, 4); Gadus macrocephalus (7); Glyptocephalus cynoglossus (7); Hippoglossoides platessoides (2); Limanda ferrugineus (7); Mallotus villosus (5, 6, 7); Melanogrammus aeglefinus (7); Myoxocephalus octodecemspinosus (7); Myoxocephalus scorpius (7); Nezumia bairdii (7); Pseudopleuronectes americanus (7); Raja spp. (7); Reinhardtius hippoglossoides (7); Theragra chalcogramma (1); Urophycis tenuis (7) Distribution: Atlantic, Pacific Records: 1. Berland 1981 (PA); 2. McClelland et al. 1983 (AT); 3. McClelland et al. 1983b (AT); 4. McClelland et al. 1984 (AT); 5. Pálsson & Beverley-Burton 1984 (AT); 6. Pálsson 1986 (AT); 7. Marcogliese 1995a (AT) ... : Published as part of Arai, Hisao P. & Smith, John W., 2016, Guide to the Parasites of Fishes of Canada Part V: Nematoda, pp. 1-274 in Zootaxa 4185 (1) on page 133, DOI: 10.11646/zootaxa.4185.1.1, http://zenodo.org/record/165530 ...